The development of domestic oil and gas industry as one of the priorities state energy policy - Karenov , R.S. (BUKETOV BUSINESS REVIEW, 2017)
It is shown that the presence of large natural resource potential leads to a special place of Kazakhstan among the industrialized countries, and its efficient use becomes a key determinant of energy security of the Republic. The significance of the resumption of oil production at the Kashagan field as an important milestone in the development of the country’s oil and gas complex is highlighted. It is proved that an important direction in the solution of questions of increase of efficiency of hydrocarbons usage in the future must be scientific justified its involvement in recycling. t is proved that an important direction in resolving the issues of increasing the efficiency of the use of hydrocarbon raw materials in the future should be the scientific substantiation of its involvement in processing. The idea is stated that, as a result of the current modernization, oil refineries will enter a different qualitative level of fuel supply. The priorities of the transition to low-carbon development of the oil and gas sector enterprises are substantiated, taking into account the commitments undertaken in the field of reducing greenhouse gas emissions in the future. Particular attention is paid to the new vector of development of the oil and gas industry, aimed primarily at technological modernization of its enterprises. It is emphasized that the work on diversification of oil transport routes allowed expanding the technical capabilities of the export of domestic oil. The need for a successful implementation of the project for the creation of an international oil consortium «Eurasia» is disclosed. It is noted that this project is aimed at exploration of deep deposits of the Caspian depression and is already entering the stage of practical implementation.